Gnielinski method in calculating the heat transfer coefficient for metallic solar tower absorber - Zulfattah, Z. M; Rafeq, Saleman Abdul; Shukri, Z. M.; Ridhwan, J.; Hanafi, M. H. M; Norain, I; Huzaimi, Z. N.; Najib, A. M. (2013)
This work is done to calculate the heat transfer coefficient of metallic wire mesh to air in an open volumetric thermal absorber. It is aimed to replace the actual ceramic with metallic which latter has better thermal properties in order to increase the efficiency of the concentrating solar power plant. The calculation of the heat transfer coefficient from porous wire structure to the air has been conducted to pursue the purpose. The structure that has been chosen is a set of metallic wires with aligned and shifted configurations. The variations of wire diameter together with various porosities from 0.10 to 0.50 have been calculated to obtain the best configuration for the absorber. The flow characteristic within the mesh structure in terms of Reynolds number and its relationship with the heat transfer coefficient has been obtained. The condition on mass flow rate of heat transfer medium and other aspects which influence the heat transfer are also discussed.